Neurotoxic astrocytes express the d-serine synthesizing enzyme, serine racemase, in Alzheimer's disease - Balu, Darrick T.; Pantazopoulos, Harry; Huang, Cathy C.Y.; Muszynski, Kevin; Harvey, Theresa Lynn; Uno, Yota; Rorabaugh, Jacki M.; Galloway, Claire R.; Botz-Zapp, Christian; Berretta, Sabina; Weinshenker, David; Coyle, Joseph T. (Neurobiology of disease, 2019)
Although β-amyloid plaques are a well-recognized hallmark of Alzheimer's disease (AD) neuropathology, no drugs reducing amyloid burden have shown efficacy in clinical trials, suggesting that once AD symptoms emerge, disease progression becomes independent of Aβ production. Reactive astrocytes are another neuropathological feature of AD, where there is an emergence of neurotoxic (A1) reactive astrocytes. We find that serine racemase (SR), the neuronal enzyme that produces the N-methyl-d-aspartate receptor (NMDAR) co-agonist d-serine, is robustly expressed in A1-reactive neurotoxic astrocytes in the hippocampus and entorhinal cortex of AD subjects and an AD rat model. Furthermore, we observe intracellular signaling changes consistent with increased extra-synaptic NMDAR activation, excitotoxicity and decreased neuronal survival. Thus, reducing neurotoxic d-serine release from A1 inflammatory astrocytes could have therapeutic benefit for mild to advanced AD, when anti-amyloid strategies are ineffective. •Serine racemase synthesizes d-serine, a potent co-agonist at NMDA receptors.•In Alzheimer's disease, abundant reactive astrocytes express serine racemase.•Serine racemase–positive reactive astrocytes express A1-type neurotoxic markers.•TgF344-AD rats show increased activation of extrasynaptic NMDA receptors.•Thus, astrocytic d-serine may promote neuronal degeneration in Alzheimer's disease.